Comparison of selected lower limb biomechanical variables between university of ibadan sportsmen with and without patellofemoral pain syndrome - Fabunmi, Ayodeji Ayodele; Oladipupo, Samson Oluwaseyi (Journal of Sports Medicine and Therapy, 2019)
Patellofemoral pain syndrome is common among athletes who participate in jumping, running and pivoting sports. The aim of this study was to compare selected lower limb biomechanical variables between University of Ibadan students (athletes) with and without patellofemoral pain syndrome. The research design for this study was a case control survey and a purposive sampling technique was used to recruit participants. Two hundred and twenty two (191(85.8%) males and 31 (14.2%) females) sportsmen participated in this study. The participants’ age was between 20-29 years. Fourty sportsmen tested positive to Clarke’s test while 27 sportsmen tested positive to Eccentric step test. Measurements of static quadriceps angle, hamstring tightness and navicular height were taken for all participants. Data were analyzed using descriptive statistics of mean, standard deviation, percentages and inferential statistics of Independent ‘t’ test. The mean lower limb biomechanical variables of participants with patellofemoral pain syndrome were 13.18 ± 2.37°, 106.46 ± 16.11° and 1.21 ± 0.61 cm while those without were 13.65 ± 2.46°, 128.95 ± 25.36° and 1.03 ± 0.58 cm for static quadriceps angle, hamstring tightness and navicular height respectively. There was no significant difference (p > 0.05) in selected lower limb biomechanical variables between participants with and without patellofemoral pain syndrome. In conclusion there was no significant difference in static quadriceps angle, hamstring tightness and ankle pronation between participants with and without patellofemoral pain syndrome. It was recommended that PFPS development is probably multifactorial with other functional disorders of the lower extremity apart from the selected variables.